Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Step-by-step explanation:
[tex]f(x) = {x}^{4} + 4 {x}^{3} - 2 {x}^{2} + 11x - 6[/tex]
[tex]f(3) = {3}^{4} + 4. {3}^{3} - 2. {3}^{2} + 11.3 - 6[/tex]
[tex]f(3) = 81 + 4.27 - 2.9 + 33 - 6[/tex]
[tex]f(3) = 81 + 108 - 18 + 33 - 6[/tex]
[tex]f(3) = 198[/tex]
Answer:
198
Step-by-step explanation:
x4 + 4x3 - 2x2 + 11x - 6 for x = 3
3^4 + 4 * 3^3 - 2 * 3^2 + 11 * 3 - 6 =
81 + 4 * 27 - 2 * 9 + 11 * 3 - 6 =
81 + 108 - 18 + 33 - 6 =
198
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.